ChatGPT and healthcare: is the future already here? Opportunities, challenges, and ethical concerns. A narrative mini-review - Venosa, Michele; Romanini, Emilio; Cerciello, Simone; Angelozzi, Massimo; Graziani, Manuel; Calvisi, Vittorio (Acta Biomedica Atenei Parmensis, 2024)
ChatGPT is an artificial intelligence (AI) powered chatbot trained on vast human language databases able to generate human-like answers to a wide variety of questions and topics. It uses natural language processing and machine learning algorithms to understand and answer users’ questions simulating human interaction. ChatGPT has recently received wide attention for its performance in different areas of common life and it can be perfectly used in healthcare with great perspectives. It can improve patient outcomes, increase efficiency, disseminate medical knowledge, and has the potential to transform healthcare since it continues to evolve and play an increasingly important role. In this paper we analyze how this technology can impact healthcare and revolutionize the traditional approach to Medicine, by examining the opportunities for patients and health professionals (including medical education, research, and academic scientific production), but also the challenges and ethical issues concerning its use. We are at the very beginning of a new era, filled with light and shadow, and further improvements and regulations are needed to ensure its proper use in healthcare.